A qualitative exploration of the mechanisms, pathways and public health outcomes of a city centre 20mph speed limit intervention: The case of Belfast, United Kingdom. (July 2021) - Cleland, Claire L.; Baker, Graham; Turner, Kieran; Jepson, Ruth; Kee, Frank; Milton, Karen; Kelly, Michael P.; Nightingale, Glenna; Hunter, Ruth F.
Abstract: Twenty miles per hour (mph) speed limits can impact the health of the public (e.g., road safety, active travel). However, a better understanding of how individuals experience 20mph limits is required, to ensure interventions are cognisant of perceptions and potential un/intended outcomes. Focus groups (n = 9, 60 participants) to explore the Belfast 20mph intervention highlighted divergent perspectives and experiences including: 12 mechanisms (e.g., limited awareness), 15 pathways (e.g., reduced driving speed→improved liveability) and 10 public health outcomes (e.g., increased cyclist safety). Future interventions should consider un/intended outcomes and implement strategies to enhance effectiveness and mitigate harms (e.g., through training, enforcement). Highlights: 20mph limits operate at a population level with a range of public health outcomes. 20mph limits resulted in 15 pathways and 10 public health outcomes being described. A range of unintended outcomes and potential harms of 20mph limits were described. Future 20mph interventions require strategies to mitigate unintended outcomes.